Exploration of the Application of Computer Image Processing Technology - Li, Xiangyu; Liu, Yanyan (Journal of Theory and Practice of Management Science, 2025)
This article explores in depth the widespread application of graphic and image processing technology in different media.Firstly, we introduced the basic concepts of graphic and image processing, the characteristics and properties of digital images, and common image file formats, establishing a technical foundation for readers.Next, we analyzed the specific applications of graphic and image processing technology in web design, paper media, and 2D animation production, including its key roles in image editing, promotional material production, character design, storyboard creation, and animation rendering.Finally, we summarized the importance of graphic and image processing technology, emphasizing its innovation and efficiency advantages in the creative industry.Through these application explorations, we demonstrate the diversity and wide range of application areas of graphic and image processing technology, providing readers with a deep understanding of this technological field.